Resection of cerebral gangliogliomas causing drug-resistant epilepsy: short- and long-term outcomes using intraoperative MRI and neuronavigation - Sommer, Bjoern; Wimmer, Cornelia; Coras, Roland; Blümcke, Ingmar; Lorber, Bogdan; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2015)
OBJECT Cerebral gangliogliomas (GGs) are highly associated with intractable epilepsy. Incomplete resection due to proximity to eloquent brain regions or misinterpretation of the resection amount is a strong negative predictor for local tumor recurrence and persisting seizures. A potential method for dealing with this obstacle could be the application of intraoperative high-field MRI (iopMRI) combined with neuronavigation. METHODS Sixty-nine patients (31 female, 38 male; median age 28.5 ± 15.4 years) suffering from cerebral GGs were included in this retrospective study. Five patients received surgery twice in the observation period. In 48 of the 69 patients, 1.5-T iopMRI combined with neuronavigational guidance was used. Lesions close to eloquent brain areas were resected with the implementation of preoperative diffusion tensor imaging tractography and blood oxygenation level-dependent functional MRI (15 patients). RESULTS Overall, complete resection was accomplished in 60 of 69 surgical procedures (87%). Two patients underwent biopsy only, and in 7 patients, subtotal resection was accomplished because of proximity to critical brain areas. Excluding the 2 biopsies, complete resection using neuronavigation/iopMRI was documented in 33 of 46 cases (72%) by intraoperative imaging. Remnant tumor mass was identified intraoperatively in 13 of 46 patients (28%). After intraoperative second-look surgery, the authors improved the total resection rate by 9 patients (up to 91% [42 of 46]). Of 21 patients undergoing conventional surgery, 14 (67%) had complete resection without the use of iopMRI. Regarding epilepsy outcome, 42 of 60 patients with seizures (70%) became completely seizure free (Engel Class IA) after a median follow-up time of 55.5 ± 36.2 months. Neurological deficits were found temporarily in 1 (1.4%) patient and permanently in 4 (5.8%) patients. CONCLUSIONS Using iopMRI combined with neuronavigation in cerebral GG surgery, the authors raised the rate of complete resection in this series by 19%. Given the fact that total resection is a strong predictor of long-term seizure control, this technique may contribute to improved seizure outcome and reduced neurological morbidity.
EVALuna2:7260